Sustained Virologic Response of 91% in Patients Infected with HCV Treated with DCV-TRIO - Rizzo, Toni (MD Conference Express, 2014)
Daclatasvir is a pangenotypic (genotypes [GT] 1–6 in vitro and GT 1–4 in clinical trials) NS5A inhibitor with a low potential for drug-drug interactions. It is approved in Europe and Japan, and it is under regulatory review in the United States. The aim of the phase 3 UNITY-1 trial [NCT01979939] was to evaluate this all-oral, ribavirin-free combination in noncirrhotic treatment-naïve and treatment-experienced patients with hepatitis C virus (HCV) genotype (GT) 1 infection.